Common National Curricular Base and the digital culture: discussions on pedagogical practice - Niz, Claudia; Vendramini Sato, Milena Aparecida; Lazaro, Adriana; Rodrigues Tezani, Thais Cristina [UNESP] (Univ Federal Sergipe, 2021)
This article aims to identify and analyze the conceptions of teachers about the competence of digital culture present in the Common National Curriculum Base (BNCC). To achieve this purpose, we chose a research of quanti-qualitative approach, with construction of a theoretical framework around the themes: Digital Information and Communication Technologies (ICT), BNCC and Digital Culture. A digital, semi-open-ended questionnaire composed of 13 questions was applied, with the participation of 124 teachers working in Basic Education, in the first semester of 2020. The results were organized, analyzed and interpreted based on the guidelines of Bardin (2011), which showed that 94% of the participating subjects work in public schools and 66% understand the digital culture as a technological tool. Thus, the data indicate the importance of debates about this theme, aiming to bring advances to the field of study and greater integration of ICT to the school curriculum.
Keywords: Common National Curricular Base (BNCC); Digital Culture; Digital Information and Communication Technologies (DICT)